Funkcjonowanie mechanizmu wczesnego ostrzegania w latach 2010-2016 i perspektywy jego reformyearly warning system - Michał Dulak (Ksiegarnia Akademicka Publishing, 2019)
The Functioning of the Early Warning System in the Years 2010‑2016 and Prospects for Its Reform During the Convention on the future of Europe and subsequent intergovernmental conferences in 2003‑2004 and 2007, high hopes were associated with the Early Warning System (EWS) in subsidiarity control procedures. Today, the main complaint formulated against EWS is its low efficiency, and at least its unused potential. Three executions of the yellow card procedure and the failure to run the orange card procedure seems to confirm the complaint. The results of institutional and statistical research presented in the article confirm that EWS instruments, such as reasoned opinions and the mechanisms of yellow and orange cards lose their attractiveness over more flexible instruments such as political dialogue with the European Commission and the so called contribution tool within the relation with the European Parliament. The reason for this is the difficulty in obtaining the required number of votes by national parliaments, but also the lack of uniform criteria for examining the principle of subsidiarity within national legislatures. The article also presents current debate on improving the EWS mechanism and introducing new procedures such as the “green card”.